Budaya Megedong-Gedongan Dapat Menurunkan Kecemasan Ibu Selama Kehamilan Di Desa Kubutambahan - Bukian, Putu Agus Windu Yasa (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
Pregnant women are prone to anxiety, which can lead to discomfort during pregnancy and childbirth. A Balinese Hindu tradition involves the megeong-gedongan ceremony. This ceremony is performed for pregnant women between the fifth and sixth months of pregnancy. The purpose of this study was to determine differences in maternal anxiety before and after the megeong-gedongan ceremony. This quantitative research method used a one-group pre-post test. The sample consisted of all pregnant women in Kubutambahan Village, meeting the agreed-upon research criteria. The research instrument was an anxiety questionnaire, which was used to observe pregnant women undergoing the megeong-gedongan ceremony. The minimum sample size was 38 pregnant women. The results showed a Z-score of -3.79, indicating that the anxiety levels before the megeong-gedongan ceremony were higher than after the megeong-gedongan ceremony. This result was statistically significant, with a p-value of <0.05, indicating that the differences before and after the megedong-gedongan ceremony were significant and effective in reducing anxiety in pregnant women, thus improving their preparedness for childbirth. The conclusion is that the megedong-gedongan technique is effective in reducing anxiety in pregnant women.